Contemporary Topics about Phosphorus in Biology and Materials - Churchill, David G.; Dutour Sikirić, Maja; Čolović, Božana; Füredi Milhofer, Helga (IntechOpen, 2020)
This book addresses a diverse set of topics regarding phosphorus chemistry, namely phosphates and closely related chemical systems. Divided into two sections, chapters cover such topics as phosphate dynamics and phosphates in biomaterials. This volume is a useful reference for scholars and researchers and will inspire readers to make future discoveries in the field.